Institutional differences and threats to international tourists from the perspective of new institutional economics - Sukiennik, Jakub; Czetwertyński, Sławomir; Przysada-Sukiennik, Paula; Mroczek-Czetwertyńska, Agnieszka (Research Papers in Economics and Finance, 2024)
The main aim of this article is to demonstrate theoretical connections in the context of institutional differences for the international tourist, which may constitute a source of threats due to institutional differences between countries. The article highlights theoretical threats stemming from institutional differences for international tourists from the perspective of new institutional economics, the research methods of which provide the analytical framework for this analysis. The post-pandemic period could transform preferences among international tourists, who are increasingly drawn to countries with significant cultural diversity. This creates dangers arising from institutional differences that may affect their sense of security and, consequently, have implications for social costs significant to the industry, as demonstrated during the COVID-19 pandemic, underscoring its crucial role in global economic development.